2020
DOI: 10.1038/s41396-020-0651-1
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiota contributes to the development of Staphylococcus aureus-induced mastitis in mice

Abstract: Mastitis is one of the most prevalent diseases in dairy farming worldwide. The gut microbiota plays an important role in the regulation of systemic and local inflammatory diseases, such as mastitis. However, the regulatory mechanism of the gut microbiota on mastitis is still unclear. Thus, the aim of this study was to investigate the function and regulatory mechanisms of the gut microbiota in host defense against mastitis caused by Staphylococcus aureus (S. aureus) infection. Increased blood-milk barrier perme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
189
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(203 citation statements)
references
References 49 publications
13
189
0
1
Order By: Relevance
“…In addition, the milk from some of the mammary glands had a foul odor. These clinical symptoms were consistent with previous reports (33)(34)(35). These characteristics further confirmed the successful establishment of a mouse mastitis model that could be used in the subsequent rifaximin pharmacodynamic studies.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the milk from some of the mammary glands had a foul odor. These clinical symptoms were consistent with previous reports (33)(34)(35). These characteristics further confirmed the successful establishment of a mouse mastitis model that could be used in the subsequent rifaximin pharmacodynamic studies.…”
Section: Discussionsupporting
confidence: 91%
“…Besides the higher A:P ratio, we found a lower concentration of butyrate in MA cows than that in SC cows ( Table 2 ). Butyrate might play a central role in modulating the inflammatory response [ 30 ] and may have a protective effect on the blood–milk barrier and reduce the severity of mastitis as observed in mice [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, knowing the abundance of certain gastrointestinal bacteria can be used for the classification or prediction of the statuses of dairy cows [ 13 , 14 ]. Recently, Hu et al [ 15 ] demonstrated that gut microbiota act as protective factors in the host defense system against mastitis in mice and that the gut–mammary gland axis represents a new and promising therapeutic approach for the treatment of mastitis. Indeed, Ma et al [ 16 ] further confirmed that the transplantation of fecal microbiota from cows affected by mastitis to germ-free mice led to mastitis symptoms, indicating that the dysbiosis of gut bacteria may lead to mastitis.…”
Section: Introductionmentioning
confidence: 99%
“…However, in vitro results frequently overestimate in vivo findings ( 40 ). Factors of animal model such as individual microbiome or virulence are determinants ( 41 , 42 ).…”
Section: Introductionmentioning
confidence: 99%